Intracranial hemorrhage in hemorrhagic disease of the newborn - Irawan Mangunatmadja; Rina W Sundariningrum; Hardiono D Pusponegoro; Endang Windiastuti (Paediatrica Indonesiana, 2003)
Background Hemorrhagic disease of the newborn (HDN) repre-sents a special case of vitamin K deficiency because the four vita-min K-coagulation factors (factors II,VII,IX,X) are already at physi-ologically low levels in the newborn. It responds to vitamin Ktherapy.Objective The aim of this study was to review the incidence, clini-cal manifestation, and outcome of HDN.Methods This was a retrospective cross sectional study on 22patients hospitalized for HDN in the Department of Child Health,Cipto Mangunkusumo Hospital from January 1997 until Decem-ber 2001. Data were obtained from medical records.Results The commonest age group (17 out of 22) was 1–3 month-old. Normal delivery was found in 19 patients and only 3 patientsreceived prophylaxis vitamin K. Almost all of them (20 out of 22)were exclusively breastfed. Seizure, pallor, decreased conscious-ness, and bulging of the anterior fontanel were significant clinicalmanifestations found in 21, 21, 13, and 9 patients respectively.Based on brain USG and/or CT scan, intracranial hemorrhage wasfound in 19 patients. Six out of 22 patients died and 7 patientssurvived with handicapConclusion Intracranial hemorrhage due to vitamin K mostly oc-curred at the age of 1 to 3 month-old. The commonest clinical mani-festations were seizure, pallor, decreased consciousness, andbulging of the anterior fontanel. Prevention by giving vitamin K rou-tinely to all newborn babies is recommended